Validation of Significant Varieties and Crop Management Practices of Mustard (Brassica juncea) at Farmer Fields in Transitional Plain of Luni Basin of Rajasthan - Sharma, N K (Annals of Arid Zone, 2016)
A study was carried out to validate the varieties and crop management practices of mustard at farmer’s fields in Transitional Plain of Luni Basin of Rajasthan. Varieties Urvashi, RRN-505, GM-2 and JM-1 provided higher grain yield than average. Seed soaking in 500 ppm thiourea for 4 hrs before sowing and foliar spray of 1000 ppm thiourea at flowering and grain filling stages enhanced mustard yield by 18.93% and 21.71%, respectively; however, foliar spray of 100 ppm salicylic acid provided 12.88% yield enhancement. Application of recommended dose of fertilizers 60 kg N and 40 kg P per hectare provided 22.95% higher yield over farmer’s practice. Foliar fertilization of 1.0% soluble NPK at flowering stage also enhanced mustard grain yield. Soil application of gypsum @ 250 kg ha-1 enhanced mustard yield by 21.51% under irrigated problematic soil and water situations